The effect of surface functionalization of PLGA nanoparticles by heparin- or chitosan-conjugated Pluronic on tumor targeting - Chung, Yong-Il; Kim, Jong Chul; Kim, Young Ha; Tae, Giyoong; Lee, Seung-Young; Kim, Kwangmeyung; Kwon, Ick Chan (ELSEVIER SCIENCE BV, 2010)
The poly (lactide-co-glycolide) (PLGA)-based nanoparticles, coated by the heparin- or chitosan-Pluronic conjugate, were used to improve a relatively low tumor-targeting efficiency of the bare PLGA nanoparticles. The prepared nanoparticles were in the size range of 100-150 nm, and the surface exposure of the functional moiety (heparin or chitosan) was confirmed by negatively or positively increased zeta potential values, respectively. The viability tests for both normal and tumor cells displayed minimal cytotoxicity of the nanoparticles. The stable surface coating, which was evident from no change in the size distribution profiles in spite of the surface charge changes in serum environment, effectively provided the desired functionalized surface that clearly enhanced the in vitro cellular uptake of the nanoparticles for both heparin and chitosan functionalization. The in vivo tumor model study, which was carried out in SCC7 tumor-bearing athymic mice, demonstrated that there was a limited, but positive effect of surface functionalization, more effective for chitosan functionalization. The accumulation of chitosan-functionalized PLGA nanoparticles in tumor was 2.4 folds higher than that of the control, PLGA nanoparticles coated with bare Pluronic, and the accumulation in liver was lower than the control. In the case of heparin functionalization, the mean value was 2.2 folds higher than that of the control, but the accumulation in liver was similar to that of the control. Therefore, the surface-functionalization by the chitosan- or heparin-conjugated Pluronic may be an effective approach for the hydrophobic nanoparticle systems aiming for the enhanced tumor imaging and therapy. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: SELF-ASSEMBLED NANOPARTICLES; IN-VIVO; BIOLOGICAL INTERACTIONS; ANTITUMOR-ACTIVITY; BLOCK-COPOLYMERS; CANCER-THERAPY; DRUG-DELIVERY; CELLS; DOXORUBICIN; MICELLES